O Departamento Nacional do Trabalho (DNT) e a organização sindical na Era Vargas (1931-1945) - Silva, Cleverson Rodrigues da (Universidade do Vale do Rio dos Sinos, 2008)
This study had its focus about the DNT – Nacional Work Department actuation in the process of unionize during the President Vargas age. DNT is an organ which bonds to Work Ministry and is responsable, after 1931, to recognize and organize the brazilian workers in trade union. This process of trade union organization could be made through several decrees and trade union laws which allowed to the Public Power, during fifteen years that Getulio Vargas was president to keep the guardian ship of brazilian workers because the trade union was free only to institution which were recognized by government and only these could defend the workers who were unionize when must fight with government institutions. This study has three chapters. The first chapter make a redeem of social and trade union legislation at First Republic to show how happened the workers moviment and the government about Work and Capital. Although is an independent chapter, it is very important to understand this question at the age before 1930 to think better about the events which happen after this time. The second chapter make analysis of the actuation of DNT and its relationship between institution and trade union. The third chapter wants to understand through workers newspapers, how were the reaction of workers about the control of trade union by DNT. It was possible identify the evolution of thinking between the workers, which were not whithout the knowledge. They fighted to construct a official trade union organization because they believe that only so they could be strong in this occuppation, conscious of their rights and owes.
Keywords: DNT; Sindicatos; Operários; Estado; Jornais operários; Trade union; Workers; Institution; Worker newspaper; ACCNPQ::Ciências Humanas::História